Reprogramming and transdifferentiation for cardiovascular development and regenerative medicine: where do we stand? - Antje D Ebert; Sebastian Diecke; Ian Y Chen; Joseph C Wu (EMBO Molecular Medicine)
Abstract Heart disease remains a leading cause of mortality and a major worldwide healthcare burden. Recent advances in stem cell biology have made it feasible to derive large quantities of cardiomyocytes for disease modeling, drug development, and regenerative medicine. The discoveries of reprogramming and transdifferentiation as novel biological processes have significantly contributed to this paradigm. This review surveys the means by which reprogramming and transdifferentiation can be employed to generate induced pluripotent stem cell‐derived cardiomyocytes (iPSC‐CMs) and induced cardiomyocytes (iCMs). The application of these patient‐specific cardiomyocytes for both in vitro disease modeling and in vivo therapies for various cardiovascular diseases will also be discussed. We propose that, with additional refinement, human disease‐specific cardiomyocytes will allow us to significantly advance the understanding of cardiovascular disease mechanisms and accelerate the development of novel therapeutic options.